Vaccine efficacy against Indonesian Highly Pathogenic Avian Influenza H5N1: systematic review and meta-analysis. Issue 37 (5th September 2017) - Villanueva-Cabezas, Juan P.; Coppo, Mauricio J.C.; Durr, Peter A.; McVernon, Jodie
Abstract: Indonesia has implemented multiple strategies to control Highly Pathogenic Avian Influenza H5N1 (HPAI/H5N1), including the licensure and use of multiple vaccine formulations. The continuous drift of Indonesian HPAI/H5N1 viruses and emergence of a new clade in 2012 that became dominant in 2016, demands the assessment of commercial vaccine formulations against Indonesian field viruses. Seven databases were explored to identify relevant literature reporting performance of commercial vaccines against Indonesian HPAI/H5N1 viruses. After methodological assessment, data were collated and analyzed to report immunogenicity and vaccine efficacy (VE) to prevent respiratory and cloacal viral shedding 2-day post challenge, and death at the end of the follow-up period. Meta-analyses were performed to assess VE consistency of alternative formulations and to explore sources of heterogeneity in VE. In total, 65 studies and 46 vaccine formulations from 13 articles were grouped per OIE's VE protocols (group 1) and variations of it (groups 2, 3, 4). We found that concurrence of vaccine-seed and challenge-viruses in a clade designation might be a better proxy of VE than current estimates based on vaccine-homologous HI antibody titers, particularly against current fourth order clade viruses (groups 1&2). Prime-boosting was efficacious across different chicken breeds (group 3), and early vaccination may increase the risk of death (group 4). One Indonesian vaccine was tested against the new dominant clade, conferring consistent protection in chickens but not in ducks. Meta-analyses revealed high inconsistency (I 2  ≥ 75%) and inefficacy of LPAI formulations against current field viruses, while potential sources of inconsistent VE were formulation of seed-homologous vaccines and the species vaccinated. We conclude that the VE of commercial vaccines in Indonesia changes as Indonesian HPAI/H5N1 evolve into new clades, which should warrant continuous matching between vaccine-seeds and emerging HPAI/H5N1. Furthermore, given the characteristics of the new Indonesian dominant HPAI/H5N1 clade, further studies to confirm VE across species are warranted.